Fusion of Bacterial Flagellin to a Dendritic Cell-Targeting αCD40 Antibody Construct Coupled With Viral or Leukemia-Specific Antigens Enhances Dendritic Cell Maturation and Activates Peptide-Responsive T Cells - Schmitt, Saskia; Tahk, Siret; Lohner, Alina; Hänel, Gerulf; Maiser, Andreas; Hauke, Martina; Patel, Lubna; Rothe, Maurine; Josenhans, Christine; Leonhardt, Heinrich; Griffioen, Marieke; Deiser, Katrin; et al. (Frontiers in Immunology, 2020)
Conventional dendritic cell (DC) vaccine strategies, in which DCs are loaded with antigens ex vivo, suffer biological issues such as impaired DC migration capacity and laborious GMP production procedures. In a promising alternative, antigens are targeted to DC-associated endocytic receptors in vivo with antibody–antigen conjugates co-administered with toll-like receptor (TLR) agonists as adjuvants. To combine the potential advantages of in vivo DC vaccination with those of conjugated TLR agonists, we generated a multifunctional antibody construct integrating the DC-specific delivery of viral- or tumor-associated antigens and DC activation by TLR ligation in one molecule. In proof-of-principle studies to determine if TLR5 ligation might improve the efficacy of such a molecule, an αCD40 antibody containing a CMV pp65-derived peptide as an antigen domain (αCD40CMV) was genetically fused to the TLR5-binding D0/D1 domain of bacterial flagellin (αCD40.FlgCMV). The analysis of surface maturation markers on immature DCs revealed that fusion of flagellin to αCD40CMV highly increased DC maturation (3.4-fold elevation of CD80 expression compared to αCD40CMV alone) by specifically interacting with TLR5. Immature DCs loaded with αCD40.FlgCMV induced significantly higher CMVNLV-specific T cell activation and proliferation compared to αCD40CMV in co-culture experiments with allogeneic and autologous T cells (1.8-fold increase in % IFN-γ/TNF-α+ CD8+ T cells and 3.9-fold increase in % CMVNLV-specific dextramer+ CD8+ T cells). More importantly, we confirmed the beneficial effects of flagellin-dependent DC stimulation using a tumor-specific neoantigen as the antigen domain. Specifically, the acute myeloid leukemia (AML)-specific mutated NPM1 (mNPM1)-derived neoantigen CLAVEEVSL was delivered to DCs in the form of αCD40mNPM1 and αCD40.FlgmNPM1 antibody constructs making this study the first to investigate mNPM1 in a DC vaccination context. Again, αCD40.FlgmNPM1-loaded DCs more potently activated allogeneic mNPM1CLA-specific T cells compared to αCD40mNPM1. These results confirmed the functionality of our multifunctional antibody construct in vitro and demonstrated that TLR5 ligation improved the efficacy of the molecule. Out data support an in vivo vaccination strategy utilizing αCD40.FlgmNPM1 for the treatment of AML, potentially in combination with other immunotherapeutic platforms such as adoptive T cell therapy or immune checkpoint blockade.